Computed Tomographic Features of Primary Small Cell Neuroendocrine Tumors of the Gallbladder. Issue 5 (September 2018) - Faraoun, Sid Ahmed; Guerrache, Youcef; Dautry, Raphael; Boudiaf, Mourad; Dohan, Anthony; Barral, Matthias; Hoeffel, Christine; Rousset, Pascal; Fohlen, Audrey; Soyer, Philippe
Abstract : Purpose: This study aimed to report the computed tomography (CT) imaging features of primary small cell neuroendocrine tumors of the gallbladder (PSCNETGs). Materials and Methods: The CT examinations of 9 patients (5 women, 4 men; median age, 57 years) with histopathologically proven PSCNETG were reviewed. Computed tomographic images were analyzed with respect to morphologic features of primary tumors and accompanying lymph nodes. Results: All PSCNETGs were visible on CT, with a median largest axial diameter of 60 mm (Q1, 30 mm; Q3 mm, 82; range, 25–86 mm). These tumors presented with extraluminal growth (8/9; 89%), heterogeneous enhancement (8/9; 89%), gallbladder replacement greater than 50% (5/9; 56%), hepatic metastases (5/9; 56%), and direct liver involvement by tumor (4/9; 44%). Enlarged lymph nodes were present in all patients (9/9; 100%) with a median largest axial diameter of 39 mm (Q1, 23 mm; Q3, 48 mm; range, 12–62 mm). Vessel encasement by lymph nodes was present in 6 (67%) of 9 patients. Conclusion: Primary small cell neuroendocrine tumors of the gallbladder predominantly presents as a large, heterogeneous gallbladder mass with extraluminal growth in association with large metastatic lymph nodes and intrahepatic metastases.